The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1756-1051.2009.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus sect. Trachycercis (Fabaceae) in Iran

Abstract: A diagnostic key, and new data are provided for seven species of Astragalus sect. Trachycercis, which occur within the area covered by the Flora of Iran. Astragalus brevipedunculatus Ranjbar is described as new, and A. armeniacus Boiss. is reported as new for the flora of Iran. The micromorphology of the seed coat surface of ten Astragalus taxa has been studied by SEM. Considerably different types of sculpturing at species level and similarities between related taxa were observed. In addition, differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The frequency ratio between A. fasciculifolius occurrence and EC indicated that the higher FR values ( Figure 5) are related to the class of <0.73 dsm -1 (4.77), suggesting the negative impact of salinity on habitat of A. fasciculifolius. Several research studies have shown the occurrence of Astragalus on non-saline soils in the mountainous parts of Iran [76][77][78]. According to the frequency ratio model results, A. fasciculifolius occurrence density is highest at the acidity (pH) ranging from 7.90 to 8.99, with FR value of 2.02.…”
Section: Fr Modelmentioning
confidence: 99%
“…The frequency ratio between A. fasciculifolius occurrence and EC indicated that the higher FR values ( Figure 5) are related to the class of <0.73 dsm -1 (4.77), suggesting the negative impact of salinity on habitat of A. fasciculifolius. Several research studies have shown the occurrence of Astragalus on non-saline soils in the mountainous parts of Iran [76][77][78]. According to the frequency ratio model results, A. fasciculifolius occurrence density is highest at the acidity (pH) ranging from 7.90 to 8.99, with FR value of 2.02.…”
Section: Fr Modelmentioning
confidence: 99%